Horsefly reactions to black surfaces: attractiveness to male and female tabanids versus surface tilt angle and temperature - Horváth, Gábor (Parasitol Res, 2020)
Tabanid flies (Diptera: Tabanidae) are attracted to shiny black targets, prefer warmer hosts against colder ones and generally attack them in sunshine. Horizontally polarised light reflected from surfaces means water for water-seeking male and female tabanids. A shiny black target above the ground, reflecting light with high degrees and various directions of linear polarisation is recognised as a host animal by female tabanids seeking for blood. Since the body of host animals has differently oriented surface parts, the following question arises: How does the attractiveness of a tilted shiny black surface to male and female tabanids depend on the tilt angle δ? Another question relates to the reaction of horseflies to horizontal black test surfaces with respect to their surface temperature. Solar panels, for example, can induce horizontally polarised light and can reach temperatures above 55 °C. How long times would horseflies stay on such hot solar panels? The answer of these questions is important not only in tabanid control, but also in the reduction of polarised light pollution caused by solar panels. To study these questions, we performed field experiments in Hungary in the summer of 2019 with horseflies and black sticky and dry test surfaces. We found that the total number of trapped (male and female) tabanids is highest if the surface is horizontal (δ = 0°), and it is minimal at δ = 75°. The number of trapped males decreases monotonously to zero with increasing δ, while the female catch has a primary maximum and minimum at δ = 0° and δ = 75°, respectively, and a further secondary peak at δ = 90°. Both sexes are strongly attracted to nearly horizontal (0° ≤ δ ≤ 15°) surfaces, and the vertical surface is also very attractive but only for females. The numbers of touchdowns and landings of tabanids are practically independent of the surface temperature T. The time period of tabanids spent on the shiny black horizontal surface decreases with increasing T so that above 58 °C tabanids spent no longer than 1 s on the surface. The horizontally polarised light reflected from solar panels attracts aquatic insects. This attraction is adverse, if the lured insects lay their eggs onto the black surface and/or cannot escape from the polarised signal and perish due to dehydration. Using polarotactic horseflies as indicator insects in our field experiment, we determined the magnitude of polarised light pollution (being proportional to the visual attractiveness to tabanids) of smooth black oblique surfaces as functions of δ and T. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s00436-020-06702-7) contains supplementary material, which is available to authorized users.